Assessments of Studentsâ Practical Skill in Laboratory: A Case Study in Second Year Chemistry Students of Bule Hora University, Ethiopia - Ligani, Shemsu; Anbessa, Baressa; Kere, Bula (EDUCARE, 2016)
ABSTRACT: Effective education should offer a balance of theoretical and practical experiences to help learners develop the competencies they need to enter professional practice and to become life-long learners throughout their careers. Laboratory activities have long had a distinctive and central role in the chemistry curriculum; and chemistry educators have suggested that many benefits accrue from engaging students in chemistry laboratory activities. The general objective of the study is to assess the practical skills of chemistry students at the BHU (Bule Hora University) in Southern Ethiopia. BHU is the newly emerged university in Ethiopia. The university is try to apply student centered approach to bring problem of surface learning in to an end and introduce deep learning, which make students critical thinker or imaginative. As a result, the university teacher educators incorporate the practical session to make learner knowledgeable, skill full, and bring attitudinal change. The data of this research was collected through questioner, focus group discussion, interview, and observation. Several problems in chemistry practical activities were identified, such as lack of confidence; shortage of time; and lack of background practical exposure, particularly on chemistry lab, lack of laboratory equipment and chemicals, lack of interest, fear of chemical toxicity, and lack of experimental freedom for independent work. In general, from the tremendous benefit of practical activities in chemistry, the authors suggested that, for example, using simulation and virtual experiments; and encouraging students to show their innate talents and make students familiar with the basic educational tool/technology.KEY WORDS: Effective Education; Chemistry Practical Activity; Students and Teachers; Lack of Confidence; Using Simulation.Â Â Â Â About the Authors: Shemsu Ligani is a Lecturer at the Department of Chemistry, Faculty of Natural and Computational Sciences BHU (Bule Hora University), Bule Hora, Ethiopia. Baressa Anbessa and Bula Kere are the Lecturers at the Department of Biology, Faculty of Natural and Computational Sciences BHU, Bule Hora, Ethiopia. Corresponding author is: liganishemsu@gmail.comHow to cite this article? Ligani, Shemsu, Baressa Anbessa & Bula Kere. (2016). âAssessments of Studentsâ Practical Skill in Laboratory: A Case Study in Second Year Chemistry Students of Bule Hora University, Ethiopiaâ in EDUCARE: International Journal for Educational Studies, Vol.9(1), August, pp.49-58. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-7877. Chronicle of the article: Accepted (June 22, 2016); Revised (July 15, 2016); and Published (August 30, 2016).